Excess Readmission-Based Penalty: Is arthroplasty different from the other outcomes? - Manickam, Raj N. (J Surg Orthop Adv, 2018)
Whether factors not under hospital’s control affect readmissions remains intensely debated in the context of the Centers for Medicare & Medicaid Services’ Hospital Readmission Reduction Program. We aimed to evaluate the potential effects of poverty, race and hospital volume on excess readmissions, with >3000 hospitals participating in “Hospital Compare”. We assessed correlations between ‘Excess Readmission Ratio’ for five eligible outcomes (including hip-knee arthroplasty) with the three area/hospital-level factors: poverty, race (percent of Black population), and hospital volume (number of discharges). Correlation coefficients of the ratios with race were approximately r=0.2; consistently larger than those with poverty, r=0–0.1. Volume showed r=0 to −0.5. Hip-knee arthroplasty showed unique findings: null correlation with poverty (r≈0); largest variability; and strong monotonicity with volume (r≈−0.5). Percent of Hispanic showed negligible correlations in secondary analysis. Penalty assessment and hospital profiling should consider areas with high percentages of Black population and small volume hospitals/providers of hip-knee surgery.